The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/sji.13042
|View full text |Cite
|
Sign up to set email alerts
|

Functional immune reconstitution early after allogeneic haematopoietic cell transplantation: A comparison of pre‐ and post‐transplantation cytokine responses in stimulated whole blood

Abstract: We aimed to use a novel standardized whole‐blood stimulation system to evaluate differences in the functional immune reconstitution in patients early after allogeneic haematopoietic cell transplantation (HCT). Between April and September 2018, 30 patients undergoing HCT had whole blood samples collected around day −21 (day 0 being the day of haematopoietic cell infusion) and day +28. Whole blood was transferred to TruCulture assays comprising prefilled incubation tubes with cell culture medium and a standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
2
12
1
Order By: Relevance
“…In the present study, we found monocyte counts to be associated with stimulated and unstimulated IL-8 and IL-6 release, emphasizing the potential critical role of these signaling molecules for differentiation of monocytes (IL-8) to macrophages (IL-8 and IL-6). As we found neither granulocytes nor other leukocyte subtypes to be associated with neither stimulated nor unstimulated TruCulture ® cytokine release, our results are in accordance with those by Gjaerde et al (27), namely that TruCulture ® may reveal an improved function of the immune cells and not simply increased immune cells in cancer patients. However, it should be emphasized that our study and hence results are explorative and needs confirmation in larger data sets.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found monocyte counts to be associated with stimulated and unstimulated IL-8 and IL-6 release, emphasizing the potential critical role of these signaling molecules for differentiation of monocytes (IL-8) to macrophages (IL-8 and IL-6). As we found neither granulocytes nor other leukocyte subtypes to be associated with neither stimulated nor unstimulated TruCulture ® cytokine release, our results are in accordance with those by Gjaerde et al (27), namely that TruCulture ® may reveal an improved function of the immune cells and not simply increased immune cells in cancer patients. However, it should be emphasized that our study and hence results are explorative and needs confirmation in larger data sets.…”
Section: Discussionsupporting
confidence: 92%
“…The shift from highly positive intercorrelations of induced cytokines in the LPS- and R848-induced samples before cART to less and more diverse intercorrelations have been described in another study using the TruCulture ® technique in patients with hematological diseases undergoing allogeneic hematopoietic stem cell transplantation with subsequent immune reconstruction ( 45 ). However, the mechanism behind the different cytokine correlations before and after immune reconstruction remains unclear.…”
Section: Discussionmentioning
confidence: 71%
“…A better understanding of the immunological mechanisms driving diverse COVID-19 disease trajectories is warranted to aid the management of patients with COVID-19 and identify new targets for interventions. In this prospective study, we applied a clinically implemented and standardized analysis assessing real-time whole-blood stimulated immune responses by TruCulture 34 , 46 , 47 in patients hospitalized with COVID-19. We identified early functional impairments in innate immune responses at the time of hospitalization associated with subsequent COVID-19 disease severity, and observed reconstitution of these impairments in recovering patients regardless of previous disease severity.…”
Section: Discussionmentioning
confidence: 99%